Permanent Interstitial Cesium-131 Brachytherapy in Treating High-Risk Recurrent Head and Neck Cancer: A Prospective Pilot Study - Kharouta, Michael; Zender, Chad; Podder, Tarun; Rezaee, Rod; Lavertu, Pierre; Fowler, Nicole; Thuener, Jason; Li, Shawn; Clancy, Kate; Xu, Zhengzheng; Yao, Min (Frontiers in Oncology, 2021)
Purpose/Objectives To establish the feasibility and safety of intraoperative placement of cesium-131 (Cs-131) seeds for re-irradiation in recurrent head and neck cancer (HNC). Methods Patients with resectable recurrent HNC who were deemed to have a high risk of second recurrence were eligible. Immediately after tumor extirpation, seeds were implanted in the surgical bed based on the preoperative treatment plan with intraoperative adjustment. The surgical bed and the seeds were covered with a regional flap or microvascular free flap. A CT of the neck was obtained on postoperative day 1 for evaluation of the postoperative dose distribution. Patients were followed 1 and 3 months after surgery, then every 3 months in the first 2 years. Results From November 2016 to September 2018, 15 patients were recruited and 12 patients received treatment per protocol. For the patients who had implants, the sites of initial recurrence included 10 neck alone, 1 neck and larynx, and 1 neck/peristomal. The median follow-up was 21.4 months. After surgery, patients remained hospitalized for a median of 6 days. There were no high-grade toxicities except two patients with wound complications requiring wound care. Eight patients had recurrences, three locoregional alone, three distant alone, and two with both locoregional and distant recurrences. Only one patient had an in-field failure. Five patients died, with 1- and 2-year overall survival of 75 and 58%. Conclusions Cs-131 implant after surgical resection in recurrent HNC is feasible and safe. There were no unexpected severe toxicities. Most failures were out-of-field or distant. Clinical Trial Registration ClinicalTrials.gov, identifier NCT02794675.